Impact of synthesized Zero-valance silver nanoparticles on acetylcholinesterase and xanthine oxidase: Toxicological and environmental implications - Srwa Hashim Mohammed; Ahmed Mahdi Rheima; Dhiey A. Al-aameri; Haider Kamil Zaidan; Zainab T. Al-Sharify (Case Studies in Chemical and Environmental Engineering)
Nanoparticles have several applications in commercial and pharmaceutical products owing to their exceptional antibacterial characteristics. Nonetheless, the extensive creation of nanoparticles has significant concerns regarding their toxicological and environmental effects. Acetylcholinesterase (AChE) and xanthine oxidase (XO) are important enzymes in neuroscience, toxicology, and pharmacology, which makes them good targets for studying how nanoparticles affect these areas. This study involved the synthesis of spherical silver nanoparticles (AgNPs) using ultraviolet (UV) irradiation and their subsequent characterization regarding structural and optical properties. The synthesizer technique utilized X-ray diffraction (XRD) and transmission electron microscopy (TEM) to ascertain the form and size of the nanoparticles, indicating an average diameter of approximately 20.23 nm. An enzymatic test evaluated the inhibitory effects of the synthesized Ag NPs on AChE and XO, using donepezil and allopurinol as positive controls. The results demonstrated that the Ag NPs displayed minimal enzyme inhibitory activity relative to the positive controls. This work underscores the necessity for additional research on the effects of nanoparticle interactions with essential biological systems.